11. ANALISIS PERILAKU KEJAHATAN TERORISME OSAMA BIN LADEN - Sindi, Hanan Qisthina; Windiani, Reni; Puspapertiwi, Sheiffi (Journal of International Relations, 2016)
Al-Qaeda, with Osama Bin Laden as the leader, had been known for doing a lot ofterrorism acts global-wide. This research is carried out to study about the behavior ofOsama bin Laden’s terrorism acts and to explain the factors influencing such behavior andacts. To achieve that purpose, this research employs qualitative method using thePsychosicial Principles provided by Luis de la Corte et.all. as the analytical tool. The studyfound that Osama Bin Laden’s terrorism acts were influenced by at least 5 among 7 factorstabled by de La Corte. These factors are minority interest, interaction and socialenvironment, coorperation with other groups based on common interests, facilities forsupporting terrorism, and ideology accepted by the public.